Biointerface design for vertical nanoprobes - Elnathan, Roey (2022)
Biointerfaces mediate safe and efficient cell manipulation, which is essential for biomedical innovations in advanced therapies and diagnostics. The biointerface established by vertical nanoprobes — arrays of vertical high-aspect-ratio nanostructures — has emerged as a simple, controllable and powerful tool for interrogating and manipulating cells. Vertical nanoprobes have substantially improved our ability to control and characterize the intracellular environment, guide biophysical stimuli with nanoscale precision to defined cell compartments, stimulate and record the electrical activity of cells, and transport hard-to-deliver drugs. These capabilities are enabling substantial advances in bioelectronics, spatiotemporally resolved molecular diagnostics, and cell and gene therapy — all underpinned by the design versatility of the nanoprobe biointerface. This Review discusses how the design of a vertical nanoprobe biointerface determines its ability to interrogate and control a cell.